The University and Its Role in Empowering People with Special Needs in Society: A Sociological Analytical Study - Abdul-Amir, Asst.L.. Fatima Al-Zahra Adnan Abdul-Amir (Sulaimani Journal for Humanities, 2026)
Universities are considered among the pioneering educational institutions that play a vital role in empowering individuals with special needs by providing a supportive learning environment and specialized services. Universities can help these individuals realize their full potential and effectively contribute to society. The process of empowering students with special needs takes various forms, including social and psychological empowerment through environmental accommodations and educational empowerment. Generally, empowerment aims to eliminate stereotypical societal and institutional processes, attitudes, and behaviors that marginalize vulnerable groups and place them in lower social ranks. Furthermore, empowerment involves providing a strong knowledge infrastructure for people with special needs and strengthening their social networks, enabling them to integrate fully into society. Empowerment here means expanding the capabilities and talents of individuals, especially those with special needs, so that they can participate in decision-making processes in universities that affect their lives, making these universities more responsive to their needs, removing social exclusion, and providing social opportunities for all. Education is considered a fundamental need in society overall and particularly for students with special needs. Through education, these students transition to a new life that helps them understand and cope positively with their disabilities, enabling them to overcome crises, challenges, and obstacles that impede their progress, especially in comparison to their non-disabled peers. Education thus opens many opportunities for students with special needs to thrive and succeed.
Keywords: university; people with special needs; society; overcoming crises